Local and global spatio-temporal sensitivity analysis of thermal consolidation around a point heat source. (March 2021) - Chaudhry, Aqeel Afzal; Buchwald, Jörg; Nagel, Thomas
Abstract: Coupled thermo–hydro-mechanical (THM) models are used for the assessment of nuclear waste disposal, reservoir engineering, and many other branches of geotechnical engineering. Model-based decision making and optimization often entail sensitivity analyses (SA) and uncertainty quantification (UQ). The suitability of different UQ and SA methods for coupled THM problems on an engineering scale requires clarification. To provide such guidance without the need for large numerical studies, an analytical solution of a simple THM problem is employed here that encompasses the most relevant primary couplings, can robustly cover the entire parameter space, and remains computationally inexpensive. Both local (OVAT) and global sensitivity analysis (GSA) techniques are applied to the study of the THM model. The information that can be derived from the different approaches is then systematically assessed, such as parameters and interactions that control selected observation quantities and how their effect varies in both space and time. We provide application-oriented conclusions on the conditions which should be met when applying the different methods as well as examples for possible misinterpretations. The analysis can serve as a benchmark for UQ and SA software designed around numerical THM simulators. This work may also serve as an attempt to highlight the methodology and effectiveness of SA to the audience from an engineering background.